Black Cloud - Hermes, Patricia (Horse diaries ;, 2012)
Despite the dangers, Black Cloud enjoys his life as a wild mustang colt in 1951 Nevada but when humans round up and slaughter his herd, he is rescued by a talkative girl named Annie who gives him a safe and comfortable life, lacking nothing but freedom.